2013
DOI: 10.1155/2013/602987
|View full text |Cite
|
Sign up to set email alerts
|

Bioeffects of Static Magnetic Fields: Oxidative Stress, Genotoxic Effects, and Cancer Studies

Abstract: The interaction of static magnetic fields (SMFs) with living organisms is a rapidly growing field of investigation. The magnetic fields (MFs) effect observed with radical pair recombination is one of the well-known mechanisms by which MFs interact with biological systems. Exposure to SMF can increase the activity, concentration, and life time of paramagnetic free radicals, which might cause oxidative stress, genetic mutation, and/or apoptosis. Current evidence suggests that cell proliferation can be influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
151
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 93 publications
3
151
2
1
Order By: Relevance
“…The persistence of induced DNA damage is a key issue when assessing residual genotoxic risk. [23][24][25] It depends on the efficacy of DNA repair, which relates to the amount of DNA breaks. 26 This might explain the important interindividual variation in the time course of γ-H2AX decline after CMR.…”
mentioning
confidence: 99%
“…The persistence of induced DNA damage is a key issue when assessing residual genotoxic risk. [23][24][25] It depends on the efficacy of DNA repair, which relates to the amount of DNA breaks. 26 This might explain the important interindividual variation in the time course of γ-H2AX decline after CMR.…”
mentioning
confidence: 99%
“…Equation [1] is used with the properties of the magnetic particles (1) and the simulation results from COMSOL Multiphysics for the external MF to calculate the forces acting on the magnetic particles. Figure 2 shows that the magnitude of the force at all locations on the plate, which, as expected, can be observed to be larger near the electromagnets where the MF and its gradient are larger.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…MACS use involves the passage of sperm through a high power static magnetic field (SMF) of 0.5 T and up to 1.5 T [82,83]. Several researches have shown that SMF can generate some kind of effect on biological systems, as pro-inflammatory changes and increase in the generation of ROS [84][85][86], which is highly detrimental to sperm. Although the mechanism by which SMF affects cells is not well understood, some reports speculate that it might increase the activity, concentration, and life time of paramagnetic free radicals, which could ultimately produce oxidative stress, genetic mutations, and/or apoptosis [87][88][89].…”
Section: How Does Macs Work?mentioning
confidence: 99%
“…Thus, the concentration and/or lifetime of free radicals that escape from the radical pair would increase by exposure to SMF, and free radicals initiate membrane lipids, proteins and DNA damage, and may lead to apoptosis or necrosis [89,90]. The diversity of alterations reported for SMF exposure may be related to varied duration, intensity, tissue penetration, and the type of cells [86,91]. In reproductive tissues, SMF has been shown to modulate the activity of several enzymes related to oxidative stress in the testicles of exposed rats [92].…”
Section: How Does Macs Work?mentioning
confidence: 99%